Sequential use of Ad26-based vaccine regimens in NHP to induce immunity against different disease targets - Selina Khan; Nadine C. Salisch; Ana Izquierdo Gil; Satish Boedhoe; Karin Feddes-de Boer; Jan Serroyen; Hanneke Schuitemaker; Roland C. Zahn (npj Vaccines, 2022)
Abstract The adenovirus (Ad)26 serotype–based vector vaccine Ad26.COV2.S has been used in millions of subjects for the prevention of COVID-19, but potentially elicits persistent anti-vector immunity. We investigated if vaccine-elicited immunity to Ad26 vector–based vaccines significantly influences antigen-specific immune responses induced by a subsequent vaccination with Ad26 vector–based vaccine regimens against different disease targets in non-human primates. A homologous Ad26 vector–based vaccination regimen or heterologous regimens (Ad26/Ad35 or Ad26/Modified Vaccinia Ankara [MVA]) induced target pathogen–specific immunity in animals, but also persistent neutralizing antibodies and T-cell responses against the vectors. However, subsequent vaccination (interval, 26–57 weeks) with homologous and heterologous Ad26 vector–based vaccine regimens encoding different target pathogen immunogens did not reveal consistent differences in humoral or cellular immune responses against the target pathogen, as compared to responses in naïve animals. These results support the sequential use of Ad26 vector–based vaccine regimens targeting different diseases.